Human Resource Management Based on the AMO (Ability, Motivation, Opportunity) Framework in Family Businesses: A Case Study of PT SMI (International Journal of Economics and Management Research, 2026)
This study aims to explore human resource management practices based on the Ability–Motivation–Opportunity (AMO) framework in family businesses, using a case study of PT Selat Malaka Indonesia (PT SMI), which operates in the energy distribution sector. The study employs a descriptive qualitative approach with an intrinsic case study design. Data were collected through in-depth interviews, limited observation, and documentation studies involving the owner, managers, and non-family employees, and were then analyzed using thematic analysis. The results indicate that the management of ability at PT SMI develops evolutively through work-based learning, senior–junior mentoring, and unstructured external training. Employee motivation is primarily shaped by job security, a family-oriented culture, and trust, although it still faces challenges in the form of work fatigue, career stagnation, and the absence of formal performance indicators. Meanwhile, opportunity is more dominant at the operational level through the delegation of technical authority and open communication, but remains limited in strategic decision-making. These findings indicate that the AMO framework at PT SMI functions implicitly as a foundation for the sustainability of the family business, yet requires systematic strengthening so that human resource professionalization can proceed in balance with family values.